INTERPRETASI KECEPATAN GELOMBANG SEISMIK REFRAKSI TOMOGRAFI DALAM PENENTUAN LITOLOGI BAWAH PERMUKAAN DI DESA BHUANA JAYA (STUDI KASUS : PT. KHOTAI MAKMUR INSAN ABADI) - Linda, Fitria Nova; Lepong, Piter; Djayus, Djayus (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2019)
Research has been carried out to determine the subsurface lithology including rock type, rock layer thickness, weathered layer, and rock hardness level based on wave velocity seismic refraction tomography at Bhuana Jaya Village, PT. Khotai Makmur Insan Abadi by using the seismic refraction method. The measurement in this study uses the In Line technique, where geophone equipment is arranged in a straight line with 3 and 5 meters spacing between the geophone. Based on the results of study, there are two types of morphology namely hill and rice field areas. Hill area is interpreted which have lithology, the first layer has a thickness of less than 3 m with lithology in the form is soil as a weathered layer, the second layer has a thickness of less than 2 m with lithology in the form is siltstone, the third layer has a thickness is less than 9 m with lithology in the form is mudstone, and the fourth layer has a thickness of less than 9 m with lithology in the form is sandstone, where this area is located at very hard rock. While rice field areas are interpreted which have lithology, the first layer has a thickness of less than 10 m with lithology in the form is alluvium as a weathered layer and the second layer has a thickness of less than 10 m with lithology in the form is siltstone with sandstone inserts, where these areas are located at an easy to medium level of hardness.